A Polymer‐Reinforced SEI Layer Induced by a Cyclic Carbonate‐Based Polymer Electrolyte Boosting 4.45 V LiCoO2/Li Metal Batteries. Issue 13 (4th March 2020) - Hu, Rongxiang; Qiu, Huayu; Zhang, Huanrui; Wang, Peng; Du, Xiaofan; Ma, Jun; Wu, Tianyuan; Lu, Chenglong; Zhou, Xinhong; Cui, Guanglei
Abstract: Lithium (Li) metal batteries (LMBs) are enjoying a renaissance due to the high energy densities. However, they still suffer from the problem of uncontrollable Li dendrite and pulverization caused by continuous cracking of solid electrolyte interphase (SEI) layers. To address these issues, developing spontaneously built robust polymer‐reinforced SEI layers during electrochemical conditioning can be a simple yet effective solution. Herein, a robust homopolymer of cyclic carbonate urethane methacrylate is presented as the polymer matrix through an in situ polymerization method, in which cyclic carbonate units can participate in building a stable polymer‐integrated SEI layer during cycling. The as‐investigated gel polymer electrolyte (GPE) assembled LiCoO2 /Li metal batteries exhibit a fantastic cyclability with a capacity retention of 92% after 200 cycles at 0.5 C (1 C = 180 mAh g −1 ), evidently exceeding that of the counterpart using liquid electrolytes. It is noted that the anionic ring‐opening polymerization of the cyclic carbonate units on the polymer close to the Li metal anodes enables a mechanically reinforced SEI layer, thus rendering excellent compatibility with Li anodes. The in situ formed polymer‐reinforced SEI layers afford a splendid strategy for developing high voltage resistant GPEs compatible with Li metal anodes toward high energy LMBs. Abstract : A strategy of in situ constructing polymer‐reinforced solid electrolyte interphase (SEI) layers is presented. The cyclic carbonate containing polymer matrix of gel polymer electrolyte (GPE) is designed to participate in the formation of a polymer‐reinforced SEI layer, which enables high compatibility between lithium metal anode and electrolyte. The as‐investigated LiCoO2 /PCUMA‐GPE/Li metal battery exhibits excellent performance at a voltage range of 3–4.45 V.